Comparative Study of Receivable Provisions and Profit Quality under PSAK 71: Studi Perbandingan Cadangan Piutang dan Kualitas Laba Berdasarkan PSAK 71 - Nabilah, Yushi; Rahayu, Duwi (Indonesian Journal of Innovation Studies, 2025)
General Background: Financial reporting standards play a crucial role in ensuring the transparency and reliability of financial statements, especially in the insurance industry, which is heavily dependent on accurate estimation of receivable provisions. Specific Background: The implementation of PSAK 71 in Indonesia has introduced a forward-looking expected credit loss model, replacing the incurred loss approach, significantly affecting financial statement recognition and measurement. Knowledge Gap: However, there remains limited empirical evidence on how this transition influences the quality of earnings and receivable provisioning practices within insurance companies. Aims: This study aims to compare receivable provisions and profit quality before and after the implementation of PSAK 71 among insurance companies registered with the Financial Services Authority (OJK). Results: The findings reveal a noticeable adjustment in provisioning policies and a moderate improvement in earnings quality post-implementation, indicating a more prudent financial reporting approach. Novelty: This study provides new insights into the practical implications of PSAK 71 on the insurance sector’s financial performance. Implications: The results are expected to assist regulators, investors, and practitioners in understanding the broader impact of accounting standard reforms on financial stability and transparency. Highlights: Examines financial reporting changes due to PSAK 71 implementation. Reveals improved prudence in receivable provisioning post-PSAK 71. Contributes to understanding earnings quality in Indonesia’s insurance sector. Keywords: PSAK 71, Receivable Provisions, Insurance Companies, Profit Quality, Financial Reporting